SADD AL- DZARI’AT DAN KORELASINYA PADA PERMASALAHAN COVID-19 (SHAF DISTANCE) - Sri Mulyani (STIS Nahdlatul Ulama Aceh, 2020)
This study aims to examine one of the methods of ijtihad Sadd al-dzari'ah which is one of the methods of making legal decisions (istinbath al-Hukum) in Islam. Sadd al-dzari'ah is preventing everything that becomes a path of destruction. Therefore, if there is a good deed that will result in damage, then that good action should be prevented so that damage does not occur. Therefore the Sadd al-dzari'ah method is an offer that is flexible enough to deal with the problems that arise at this time. Therefore this study will discuss how Sadd al Dzari'ah's correlation on the Covid-19 problem, which focuses on the problem of shaf distance.This study aims to examine one of the methods of ijtihad Sadd al-dzari'ah which is one of the methods of making legal decisions (istinbath al-Hukum) in Islam. Sadd al-dzari'ah is preventing everything that becomes a path of destruction. Therefore, if there is a good deed that will result in damage, then that good action should be prevented so that damage does not occur. Therefore the Sadd al-dzari'ah method is an offer that is flexible enough to deal with the problems that arise at this time. Therefore this study will discuss how Sadd al Dzari'ah's correlation on the Covid-19 problem, which focuses on the problem of shaf distance.